The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.brs.2019.11.009
|View full text |Cite
|
Sign up to set email alerts
|

TMS for staging and predicting functional decline in frontotemporal dementia

Abstract: a b s t r a c tObjective: To evaluate if transcranial magnetic stimulation (TMS) measures correlate with disease severity and predict functional decline in frontotemporal dementia (FTD) phenotypes. Methods: Paired-pulse TMS was used to investigate the activity of different intracortical circuits in 171 FTD patients (122 bvFTD, 31 avPPA, 18 svPPA) and 74 healthy controls. Pearson's correlations were used to analyze the association between TMS measures and disease severity, while multiple regression analysis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 38 publications
3
17
0
Order By: Relevance
“…We also observed an association between serum GFAP concentration and indirect measures of GABAergic neurotransmission, which have been demonstrated to be impaired in FTLD (Benussi et al, 2019aPadovani et al, 2018), and reflect disease severity and progression (Benussi et al, 2020b(Benussi et al, , 2020a. We observed that the higher the serum GFAP concentration, the greater was the impairment in LICI, which is considered to reflect short-lasting postsynaptic inhibition mediated through the GABAB receptors at the level of local interneurons (Rossini et al, 2015;Ziemann et al, 2015).…”
Section: Discussionsupporting
confidence: 58%
“…We also observed an association between serum GFAP concentration and indirect measures of GABAergic neurotransmission, which have been demonstrated to be impaired in FTLD (Benussi et al, 2019aPadovani et al, 2018), and reflect disease severity and progression (Benussi et al, 2020b(Benussi et al, , 2020a. We observed that the higher the serum GFAP concentration, the greater was the impairment in LICI, which is considered to reflect short-lasting postsynaptic inhibition mediated through the GABAB receptors at the level of local interneurons (Rossini et al, 2015;Ziemann et al, 2015).…”
Section: Discussionsupporting
confidence: 58%
“…Cortex hyperexcitability as highlighted by a lower RMT, in fact, is a key feature of both ALS and FTD [ 116 ]. Same findings were replicated in a larger cohort of FTD patients using the Mini Mental State Examination test [ 117 ].…”
Section: Neurophysiological Approachesmentioning
confidence: 64%
“…SAI is not different in patients with FTD compared to healthy subjects; this is to be expected given that SAI reflects cholinergic transmission, which is not typically involved in FTD. As well as being correlated with the FTLD-CDR (a clinical rating scale to measure FTD severity), it was found that less SICI is associated with greater clinical progression of FTD (120). The interpretation was that, rather than reflecting impairments of a specific interneuron circuit, these abnormalities reflect an inability to integrate two, closely timed pulses.…”
Section: Tms Measures Correlate With Cognitive Symptoms and Predicts Functional Declinementioning
confidence: 98%
“…Early studies of CSE in patients with FTD showed no changes compared to healthy subjects (103,118). However, a series of studies by Benussi et al have investigated intracortical circuits in a large number of FTD patients, finding that both intracortical facilitation (ICF and SICF) and inhibition (SICI and LICI) are lower in FTD than in healthy controls (119)(120)(121).…”
Section: Corticospinal Excitability In Dementiasmentioning
confidence: 99%